Child Spacing and Parity Progression: Implication for Maternal Nutritional Status among Women in Ekiti Communities, Southwestern Nigeria - Adebowale, S.A.; Adepoju, O.T.; Fagbamigbe, F.A. (Pakistan Journal of Nutrition, 2011)
The evolving dynamics that face maternal health in developing countries are worrisome. The achievement of the desirable Millennium Development Goals on maternal and child health in Ekiti will remain a mirage if women nutrition is compromised. Short birth spacing and high frequency of childbearing adversely affect maternal health through maternal depletion syndrome. This study was a cross-sectional house-hold survey where a stratified multi-stage sampling technique was used to select 1450 women of childbearing age as respondents. Body Mass Index (BMI) measurement was used as indicator of nutritional status. Results showed that the median birth interval was 33.0 months. Parity progression rate was higher among under-nourished mothers and births after an interval of less than 24 months (short birth interval) was accounted for by 38.3% of undernourished mothers. Taking into account of several potentially confounding variables, the Cox-regression model showed that mothers who left birth interval of less than 24 months are 2.0 (p